Screening of Antioxidant Activity of Gentian Lutea Root and Its Application in Oil-in-Water Emulsions - Nurul Aini, Mohd Azman; Segovia, Francisco; Martínez-Farré, Xavier; Gil, Emilio; Almajano, María Pilar (MDPI AG, 2014)
Gentiana Lutea root (G. Lutea) is a medicinal herb, traditionally used as a bitter tonic in gastrointestinal ailments for improving the digestive system. The active principles of G. Lutea were found to be secoiridoid bitter compounds as well as many other active compounds causing the pharmacological effects. No study to date has yet determined the potential of G. Lutea antioxidant activity on lipid oxidation. Thus, the aim of this study was to evaluate the effects of an extract of G. Lutea on lipid oxidation during storage of an emulsion. G. Lutea extracts showed excellent antioxidant activity measured by DPPH scavenging assay and Trolox equivalent antioxidant capacity (TEAC) assays. An amount of 0.5% w/w G. Lutea lyophilise was able to inhibit lipid oxidation throughout storage (p < 0.05). A mixture of G. Lutea with 0.1% (w/w) BSA showed a good synergic effect and better antioxidant activity in the emulsion. Quantitative results of HPLC showed that G. Lutea contained secoiridoid-glycosides (gentiopiocroside and sweroside) and post column analysis displayed radical scavenging activity of G. Lutea extract towards the ABTS radical. The results from this study highlight the potential of G. Lutea as a food ingredient in the design of healthier food commodities.